Financial diversification and income generation at African universit ies - Blair, Robert D.D. (Washington, D.C : World Bank, 1992)
This copy was produced after technical note no. 2 of education and t raining division of the World Bank
AR/SIC/1/2/13
English
Shelf no. 2
Keywords: Income generation activities -- Africa